Increasing political trust through deliberative mini-publics: The role of public participation partnerships required for Sustainability - Weymouth, Robert Michael (Curtin University, 2020)
This thesis argues that rebuilding trust in government through public partnerships plays an important role in resolving the wicked problems related to transitioning to sustainability. Two mixed-methods case studies of 100% participatory budgeting ‘mini-publics’ in Australia show large improvements in participants’ political trust and satisfaction with their relationship to government. This result is used to argue that deliberative democracy can deliver the partnership relationship that builds the vital trust required for sustainability.